PKM MAHASISWA UNIVERSITAS INDO GLOBAL MANDIRI PENGEMBANGAN BISNIS THRIFTING SHOP SEPATU ONLINE - Dwi Oktarini, Rahmi; Choiriya, Nabila; Hertati, Lesi; Terttiaavini; Heryati, Agustina; Asmawati (Transpublika Publisher, 2021)
Shoes play a significant role in today's fashion and style. Consequently, consumers consider various factors such as product quality, price, and promotions when making purchasing decisions. In this regard, we, as students of Indo Global University, conducted independent research and socialization activities at the online shoe retailer